2012
DOI: 10.1177/1078087411436104
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Attachment, Social Participation, and Willingness to Stay in China’s Low-Income Communities

Abstract: Neighborhood attachment is an important factor that determines political and civic participation, which further help to enhance neighborhood stability. This article explores this argument in the context of Chinese cities. Contrary to common perception, although rural migrants do not identify themselves with the places where they live and do not actively participate in community activities, they express a relatively strong willingness to stay in these places. In contrast, the unemployed or retired urban residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 46 publications
(57 reference statements)
8
156
1
1
Order By: Relevance
“…Both neighbourhood characteristics, which sometimes coincide with each other, suggest that residential instability and lack of resources are the main causes for the lack of neighbourhood cohesion. For traditional courtyards, the prospect of demolition and relocation (Wu and He, 2005) and fast residential turnovers due to the departure of affluent residents (Wu, 2012) may have reduced the willingness of residents to invest any further into the neighbourhood such as reaching out to new neighbours. The government's recent emphasis to construct a post-industrial globalising metropolis (Wu, 2015) has further accelerated the regeneration of old neighbourhoods such as traditional courtyards in inner city of Shanghai (Zhu, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both neighbourhood characteristics, which sometimes coincide with each other, suggest that residential instability and lack of resources are the main causes for the lack of neighbourhood cohesion. For traditional courtyards, the prospect of demolition and relocation (Wu and He, 2005) and fast residential turnovers due to the departure of affluent residents (Wu, 2012) may have reduced the willingness of residents to invest any further into the neighbourhood such as reaching out to new neighbours. The government's recent emphasis to construct a post-industrial globalising metropolis (Wu, 2015) has further accelerated the regeneration of old neighbourhoods such as traditional courtyards in inner city of Shanghai (Zhu, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting lower rents in low-income neighbourhoods attracted a substantial share of rural migrant residents to live alongside natives who cannot afford to move out (Wu and He, 2005). Using data collected in low-income neighbourhoods from six different Chinese cities, Wu (2012) found that compared to the working population, unemployed residents are significantly less likely to feel attached to the neighbourhood, signalling that poverty reduces the sense of belonging of residents. In addition, migrants are also less likely to feel attached to the neighbourhood although they express the wish to stay in the locality.…”
Section: Migrant Influx and Social Cohesion In Chinese Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This individual recognition, or perception, can vary by life experience and personal characteristics (Altschuler, Somkin, and Adler 2004;Brownson et al 2009;Diez Roux 2001;O'Brien et al 2014;Roosa et al 2009;Vega et al 2011;Wachs 1999;Weden, Carpiano, and Robert 2008;Wen, Hawkley, and Cacioppo 2006;Wu 2012). Consequently, subjective neighborhood perceptions may affect the health and behavior of residents more strongly than do objective neighborhood characteristics that residents may or may not recognize (Polling et al 2014;Weden, Carpiano, and Robert 2008;Wen, Hawkley, and Cacioppo 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a survey conducted among several types of low-income communities in six Chinese cities, rural-to-urban migrants reported the least sense of neighbourhood attachment and social participation (Wu 2012). Yet, this survey and other studies have found a higher willingness to stay in their urban neighbourhoods, especially compared to earlier generations of rural-to-urban migrant workers (Hu, Xu, and Chen 2011;Liu, Li, and Breitung 2012;Wu 2012).…”
Section: Discrimination and Stigmatizationmentioning
confidence: 99%